Our Man in Madrid: Bullfighting Enters the Political Arena. Issue 2 (6th April 2022) - Wheeler, Duncan
Abstract: Four bullfighters stood as MPs in the April 2019 Spanish general elections: Miguel Abellán and Salvador Vega for the PP; and Serafín Martín and Pablo Ciprés for Vox. None was elected, although Abellán and Martín came close. The former's allegiance was rewarded with his political appointment by the PP's Isabel Díaz Ayuso as Director‐General of Madrid's Centre for Taurine Activities. Bullfighters throwing their hats into the political arena is inextricably linked to the escalation of Spain's cultural wars and critically interrogating the ongoing controversies surrounding the future of bullfighting constitutes a privileged lens through which to view increasingly visible fissures in the post‐Franco constitutional order. Using archival materials and ethnographic research alongside an interview conducted with Abellán, this article explores the interrelationship of bullfighting with the Catalan secessionist vote as well as its currency in the struggle between Vox and the PP for the conservative vote.